Feasible monitoring of the inhibitory effects of free NH3 on NO2− oxidation. Issue 5 (3rd September 2018) - Yoo, Byeong-Hak; Lee, Sang-hun
ABSTRACT: This study investigated nitrite (NO2 − ) accumulation due to FA (Free Ammonia: NH3 ) inhibition in an anaerobic-aerobic-anoxic (AOA) process reactor to mainly treat wastewater containing 302−610 mg/L of NH3 /NH4 + –N. Based on an experimental operation focusing on the nitrification, it was observed that NO2 − was accumulated in the aerobic nitrification zone as pH increased, due to inhibition of NO2 − conversion to NO3 − by FA. This result implied FA inhibition to NOB (NO2 − −Oxidizing Bacteria) for converting NO2 − to NO3 − . The objective of this study is to develop a feasible monitoring procedure for early detection of the FA inhibition toward NO2 − accumulation and poor nitrification. Thus, in order to rapidly assess FA concentrations, an NH3 probe was utilized to measure NH3 concentrations together with applying a simple model prediction using the measured NH4 + concentrations, the Henry's law constant of NH3 and measured pH. The predictive model NH3 levels were verified by a good correlation (89%) with the corresponding measured data, but the model prediction underestimated FA concentrations at less than 7.4 and a little overestimated at pH above 7.5. Interestingly, accumulated NO2 − levels were roughly correlated with FA levels that were observed at delayed time points. This reflects the detected FA levels can be good indicators of NO2 − levels with some delayed time. NO2 − accumulation started at measured FA concentrations of higher than approximately 3 mg/L and ceased below that FA level.